Pengaruh Kepemimpinan dan Disiplin Kerja terhadap Kinerja Pegawai di Kantor Koperasi Pegawai Republik Indonesia (KP-RI) Sutera Kabupaten Pesisir Selatan - Medikal Adril; Riri Mayliza (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to determine the effect of leadership and work discipline on employee performance at the KPRI Sutera Office. The problem raised in this study is the fluctuation of employee performance which is suspected to be related to leadership factors and the level of work discipline. The method used is a quantitative method with data collection techniques through observation and distributing questionnaires to KPRI employees. The results of the study indicate that leadership has a significant influence on employee performance, which means that the better the leadership applied, the higher the employee performance. In addition, work discipline also has a significant effect on performance, where employees who have a high level of discipline tend to show better productivity. This study provides a strategic contribution in answering employee performance problems, as well as providing recommendations for management to improve performance by strengthening aspects of leadership and discipline. In addition, the results of this study can also be a scientific reference in human resource management studies, especially in the cooperative sector in Indonesia.